2011
DOI: 10.2134/agronj2011.0073
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Tillage and Poultry Litter Impacts on Soybean and Corn Grain Yield

Abstract: Reduced tillage, poultry litter applications, crop rotations, and winter cover cropping are management practices that could be used with conservation tillage systems to increase yields compared to conventional monoculture systems. Th is study evaluated cropping sequences of corn (Zea mays L.), soybean [Glycine max (L.) Merr.], and corn-soybean rotations with wheat (Triticum aestivum L.) covers in conventional, strip, and no-tillage (no-till) systems, following poultry litter additions to wheat cover. Th e stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 40 publications
(37 reference statements)
3
23
0
Order By: Relevance
“…Hirzel et al (2007) found similar results with corn silage; yield averages obtained from PL additions were comparable to that of urea. Watts and Torbert (2011) also reported that soybean yields were increased 8 out of 9 years when PL was used as a nutrient source. In contrast, a 2.5-year bermudagrass field study showed that forage yield with broiler litter was 64, 48, and 67 % of yield with ammonium nitrate applied at the same N level in these three years, respectively (Woodard and Sollenberger, 2011).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hirzel et al (2007) found similar results with corn silage; yield averages obtained from PL additions were comparable to that of urea. Watts and Torbert (2011) also reported that soybean yields were increased 8 out of 9 years when PL was used as a nutrient source. In contrast, a 2.5-year bermudagrass field study showed that forage yield with broiler litter was 64, 48, and 67 % of yield with ammonium nitrate applied at the same N level in these three years, respectively (Woodard and Sollenberger, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Thus, poultry litter may be a valuable nutrient source for row crop production systems. Numerous studies have proven that poultry litter can be used as an effective fertility source (Hirzel et al, 2007;Mitchell and Tu, 2005;Reddy et al, 2004;Tewolde et al, 2009a;Watts and Torbert, 2011;Wiatrak et al, 2004). However, poultry litter may produce yields different to that of commercial fertilizer sources.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilization of soil aggregates by the use of soil amendments (or poultry litter and cover crops) can increase water-holding capacity of soils, and thus positively impact crop growth (Watts and Torbert, 2011). In a study by Kabir and Koide (2000), winter wheat increased soil aggregation compared to a winter fallow control.…”
mentioning
confidence: 99%
“…Studies comparing N accumulation using poultry litter and ammonium nitrate have demonstrated higher levels of total N as well as nitrate following poultry litter applications (Nyakatawa et al, 2001;Mitchell and Tu, 2006). In addition, cereal cover crops such as rye and winter wheat can reduce nitrate leaching by capturing N from the preceding crop (Strock et al, 2004;Costa et al, 2000); however, cereal covers may not return N to soils, resulting in no yield benefit to subsequent row crops (Watts and Torbert, 2011). However, the extent of this is unknown for long-term corn systems under no-tillage; therefore more region-specific data are needed.…”
mentioning
confidence: 99%